Measurement of neutrino and antineutrino oscillations by the T2K experiment including a new additional sample of nu(e) interactions at the far detector - Abe,K; Amey,J; Andreopoulos,C; Antonova,M; Aoki,S; Ariga,A; Ashida,Y; Ban,S; Barbi,M; Barker,GJ; Barr,G; Barry,C; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The T2K experiment reports an updated analysis of neutrino and antineutrino oscillations in appearanceand disappearance channels. A sample of electron neutrino candidates at Super-Kamiokande in which a piondecay has been tagged is added to the four single-ring samples used in previous T2K oscillation analyses.Through combined analyses of these five samples, simultaneous measurements of four oscillationparameters, jΔm232j, sin2 θ23, sin2 θ13, and δCP and of the mass ordering are made. A set of studies ofsimulated data indicates that the sensitivity to the oscillation parameters is not limited by neutrino interactionmodel uncertainty. Multiple oscillation analyses are performed, and frequentist and Bayesian intervals arepresented for combinations of the oscillation parameters with and without the inclusion of reactor constraintson sin2 θ13. When combined with reactor measurements, the hypothesis of CP conservation (δCP ¼ 0 or π) isexcluded at 90% confidence level. The 90% confidence region for δCP is½−2.95;−0.44 (½−1.47;−1.27) fornormal (inverted) ordering. The central values and 68% confidence intervals for the other oscillationparameters for normal (inverted) ordering are Δm232 ¼ 2.54 0.08ð2.51 0.08Þ × 10−3 eV2=c4 andsin2θ23 ¼ 0.55þ0.05 −0.09 (0.55þ0.05 −0.08 ), compatible with maximal mixing. In the Bayesian analysis, the dataweakly prefer normal ordering (Bayes factor 3.7) and the upper octant for sin2 θ23 (Bayes factor 2.4).